Exploring the impact of trade and investment on income inequality: a cross-national sectoral analysis of the developed countries - Mahler, Vincent A.; Roscoe, Douglas D.; Jesuit, David K. (1999)
This article explores the relationship between international integration and domestic inequality in the developed countries in the mid-1980s and early 1990s. The analysis examines two major modes of integration, trade and direct investment, disaggregating each by economic sector and distinguishing between imports and exports, and inbound and outbound flows and stocks. In measuring income inequality, extensive use is made of micro-data sets that have recently become available through the Luxembourg Income Study (LIS), which provides much more detailed and comparable data on income inequality than has heretofore been the case. In particular, LIS data can be aggregated at the level of economic sector, and permit the comparison of pre- and post-government income. The study finds few significant relationships between either trade or investment and sectoral income distribution. The overall conclusion is that economic globalization is not a critically important factor in explaining recent trends in income inequality in the Western world. - Reproduced
Keywords: Investment; Trade; Income distribution